Peningkatan Pengetahuan dan Motivasi Kader Posyandu di Bojong Menteng Melalui Webinar Gizi Saat Pandemi COVID-19 - Lina Agestika; Angga Rizqiawan; Mita Arini; Befi Sundari; Hassya Maulida; Khalissa Fathin Anshari; Putri Ayu Mulia; Ria Wati (Sekolah Tinggi Ilmu Kesehatan Baiturrahim Jambi, 2021)
The disturbance in performing Poyandu routine activities in Puskesmas Bojong Menteng and face-to-face Cadre refresher during COVID-19 pandemic might reduce cadres' motivation and knowledge. A virtual education program through webinars is one of the possible solutions. This community service activity aims to analyze the effects of webinar on nutrition through zoom meeting on cadres' motivation and knowledge regarding 1) the role of cadres during the pandemic, 2) prevention of COVID-19 with balanced nutrition, water, sanitation, hygiene, and physical activity and 3) introduction to Ms. Excel application in smartphone. The webinars were given in 2 days with delivering a pre- and post-test evaluation. The statistical analysis used was Wilcoxon signed-rank test. Participants were 33 Cadres. Cadres have received technical guidance to use the zoom application on their smartphone prior to the webinar schedule. The majority of cadres are in the age of 31-45 years old (45.5%) and have graduated from high school (63.6%). Result shows that the mean of Cadre’s score on knowledge and motivation had increased from 65 to 85 and 90 to 100 (p:<0.05). This concludes that webinars could be a potential way to refresh and educate Posyandu cadres during a pandemic